RELEVANSI AJARAN TASAWUF PADA MASA MODERN - Muzakkir Muzakkir (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract: The Relevance of Tasawuf Teachings in Modern Time.Tasawuf is a medium of getting oneself closer to God, based on the practices of the Prophet Muhammad and his Companions. In addition, the Holy Qur’an contains numerous verses urging muslims to do so. Sufi doctrines–such as zuhd, wara’, mujahadah, murâqabah, and muhasabah has in fact become part of religious traditions among Indonesians. However, they have not become essential elements of social developments. The present writer explores some aspects of tasawuf and how it becomes  relevant to contemporary situation.Kata Kunci: Tasawuf, spiritualisme, era modern